Conflict and conciliation: industrial relations in an industrialising Hong Kong, ca. 1946-1960. (4th July 2021) - Clayton, David
ABSTRACT: This article focuses on a long-standing riddle: what explains the quiescence of Hong Kong workers? Building on a literature written by social historians, industrial relations experts and social scientists, and using qualitative and quantitative data created by governments, the article discusses the effects of the de-radicalization of the working class; acute macroeconomic instability; 'paternalistic' and discriminatory labour management strategies; and interventions by the colonial state in industrial relations – most notably voluntary conciliation. The article argues that Hong Kong's dominant decentralised system of industrial relations was supported by a conciliation-based approach nurtured by the Labour Department of the colonial administration. It also notes similarities between Hong Kong's conciliation-based approach and that which emerged in 1940s Britain. New evidence on the effectiveness of conciliation qualifies the hitherto dominant thesis that British colonial administrations in Asia repressed labor activism.